Integrated Non-Digital Media Innovation ‘Space Capsule’ to Train Spatial Visualization Skills in Solid Geometry for Students - Hilma Alia; Lisnani Lisnani; Hesti Widyawati; Justin Walker; Riza Haikal Azhar (Department of Mathematics Education Program IPI Garut, 2026)
Tujuan penelitian ini menghasilkan media pembelajaran non-digital terintegrasi bernama